The sub-MIC selective window decreases along the digestive tract: determination of the minimal selective concentration of oxytetracycline in sterilised intestinal contents - Imazaki, Pedro Henrique; Voisin, Bertille; Arpaillange, Nathalie; Roques, Béatrice B.; Dordet-Frisoni, Emilie; Dupouy, Véronique; Ferran, Aude A.; Bousquet-Mélou, Alain; Bibbal, Delphine (Frontiers in Microbiology, 2024)
The administration of antibiotics can expose the digestive microbiota of humans and animals to sub-inhibitory concentrations, potentially favouring the selection of resistant bacteria. The minimal selective concentration (MSC) is a key indicator to understand this process. The MSC is defined as the lowest concentration of an antibiotic that promotes the growth of a resistant strain over a susceptible isogenic strain, representing the lower limit of the sub-MIC selective window where resistant mutants can be selected. While previous studies focused on determining the MSC under standard culture conditions, this study investigated the MSC of oxytetracycline (OTC) in Mueller-Hinton broth (MHB) and sterilised intestinal contents (SIC) from the jejunum, caecum and rectum (faeces) of pigs to approximate in vivo conditions, using two isogenic strains of Escherichia coli (one susceptible and one resistant to OTC). Additionally, the minimal inhibitory concentration (MIC) of OTC against the susceptible strain was determined to assess the upper limit of the sub-MIC selective window. Results indicated that MIC and MSC values were lower in MHB than in SIC. In the latter, these values varied depending on the intestinal segment, with distal compartments exhibiting higher MIC and MSC values. This suggests that OTC binds to digestive contents, reducing the fraction of free OTC. However, binding alone does not fully explain our results, and interactions between bacteria and intestinal contents may play a role. The sub-MIC selective window of OTC in SIC narrowed from the jejunum to the rectum, with a significantly closer MSC to MIC in faecal SIC. These findings provide initial estimates of low concentrations facilitating resistance selection in the gut. This research enhances the understanding of antimicrobial resistance selection, emphasising the intricate interplay between antibiotics and intestinal content composition in assessing the risk of resistance development in the gut.